Quo vadis, Brazil? Environmental Malgovernance under Bolsonaro and the Ambiguous Role of the Sustainable Development Goals. (21st December 2021) - Bastos Lima, Mairon G.; Da Costa, Karen
Abstract : Brazil has continuously been in the international spotlight, first as an emerging economy improving social inclusion and sustainable development, then suddenly as a global pariah on environmental governance. Using two case studies – the rising deforestation of the Amazon and the 2019 oil spill on Brazil's Northeast coast – we examine the Bolsonaro administration in the context of the UN Sustainable Development Goals, to reveal a combination of misgovernance and malgovernance, where transgressions are intentional. The article develops these analytical concepts, explores how environmental malgovernance in Brazil may be addressed and discusses how Bolsonaro's malpractices are internationally challenged, but also condoned.